Medical medium celery juice : the most powerful medicine of our time healing millions worldwide - William, Anthony (William, Anthony. Medical medium., 2019)
From celebrities posting about their daily celery juice routines to people from all walks of life sharing pictures and testimonials of their dramatic recovery stories, celery juice is revealing itself to ignite healing when all odds seem against it. What began decades ago as a quiet movement has become a global healing revolution. In Celery Juice: The Most Powerful Medicine of Our Time Healing Millions Worldwide, Anthony William, the originator of the global celery juice movement, introduces you to celery juice's incredible ability to create sweeping improvements on every level of our health: *Healing the gut and relieving digestive disorders *Balancing blood sugar, blood pressure, weight, and adrenal function *Neutralizing and flushing toxins from the liver and brain *Restoring health in people who suffer from a vast range of chronic and mystery illnesses and symptoms, among them fatigue, brain fog, acne, eczema, addiction, ADHD, thyroid disorders, diabetes, SIBO, eating disorders, autoimmune disorders, Lyme disease, and eye problems.